APLIKASI PENGELOLAAN DATA PENGUJIAN JELLY STRENGTH DAN WHITENES PADA INDUSTRI SURIMI PT.KELOLA MINA LAUT TUBAN - Nur Arini; Muhyiddin Zainul Arifin; Agus Sifaunajah (KH. A. Wahab Hasbullah University, 2016)
PT Manage Mina Seafood is a company working in the field of fisheries, particularly the freezing of fish that can be called by the term surimi , Grade is the emergence of a value of the test results together with the final result , RM or raw material or also called the raw material is bad it will display the grade with a low value , low value is impacting the sales price is very cheap , the testing manual systems are still so simple when compared with the progress of this company in this program I am using Java .Therefore I strive to create an effective new system more attractive and long term for the company , for my research this time I can give results in value can make progress on the company and accepted by the company PT.KML .Â Keywords : Surimi , Jelly strength , Grade , Java